Lean Six Sigma and environmental sustainability: the case of a Norwegian dairy producer. Issue 1 (6th March 2017) - Powell, Daryl; Lundeby, Sissel; Chabada, Lukas; Dreyer, Heidi
Abstract : Purpose: The purpose of this paper is to investigate the application of Lean Six Sigma (LSS) in the continuous process industry, taking an insight into the food processing industry; and to evaluate the impact of LSS on environmental sustainability. The authors present observations and experiences from the application of LSS at a Norwegian dairy producer, with the aim of bringing out pertinent factors and useful insights that help us to understand how LSS can contribute toward greater environmental sustainability in this industry type, something that is so far lacking in the extant literature. Design/methodology/approach: The authors adopt a single, longitudinal field study approach as we observe an entire cycle of the VSM-DMAIC (value stream mapping-define, measure, analyze, improve and control) LSS process, which evolved over a six-month period at the dairy. Findings: The authors highlight some of the important elements that should be considered when using LSS as a contributor toward greater environmental sustainability in fresh-food supply chains. The authors also present some of the specific outcomes and key success criteria that became apparent to the implementation team following the deployment of the VSM-DMAIC approach. Originality/value: The authors demonstrate how LSS can be applied in the food processing industry as a contributor to greater environmental sustainability. The authors also make useful reflections regarding the success criteria that can be used by researchers and practitioners for the effective deployment of such an approach, particularly in the continuous process industry.